Nationalsozialistische Diktatur : 1933 - 1945 ; eine Bilanz - Bracher, Karl Dietrich 1922-2016; Funke, Manfred 1939-2010; Jacobsen, Hans-Adolf 1925-2016 (Bonner Schriften zur Politik und Zeitgeschichte, 1983)
Literaturverzeichnis